Direito natural, política e liberdade em John Locke - Virgínio Filho, Sérgio Ricardo de Andrade (2017)
The present work has as it’s object of research the reading of two works by John Locke, the “Second Treaty on the Government” and the “Letter concerning Tolerance” in which the concepts of Social Contract and freedom will be discussed. The narrative of the natural state constitutes a key piece for the development of this research, considering that it presents the hypothetical initial stage of civil government. To this end, Locke takes into account that individuals enjoy a certain freedom present in the State of Nature, as each pursues the survival and satisfaction of their own interests based on the use of Reason, which is granted to each one for the persecution of the means necessary under natural laws. The concept of freedom used by Locke is analyzed based on the idea of a break with tradition and later foundations of political thought based on the autonomy of human reason. The research is eminently bibliographic and aims to investigate how John Locke defends the concept of social contract.